Transverse patterning, aging, and neuropsychological correlates in humans. Issue 12 (11th October 2016) - Gracian, Enrique I.; Osmon, David C.; Mosack, Katie E.
ABSTRACT: Transverse patterning is a learning and memory adaptation of the 'rock/paper/scissors' problem that has been though to depend on the hippocampus, is sensitive to aging, and requires pattern separation to solve. Previous investigators dichotomized cognitively normal older adults who passed a cognitive screening into impaired and unimpaired subsets, and found that impaired older adults were disproportionately deficient in pattern separation abilities. However, this variability in pattern separation ability has not been examined using a transverse patterning task. Our aims, then, were two‐fold: First, to determine if impaired older adults were inferior on transverse patterning compared to unimpaired older adults and young adults; second, to identify the neuropsychological correlates of transverse patterning. Our findings revealed that impaired older adults required more trials to criterion on the transverse patterning task than both young adults and unimpaired older adults. Unimpaired older adults also required more trials to criterion than young adults. A detailed analysis of the transverse patterning task confirmed that the aforementioned group differences were only observed in high interference conditions when pattern separation demands were at their peak. Finally, regression analyses showed that both memory and executive functioning neuropsychological composite scores were related to different indices of transverse patterning performance. Consistent with the pattern separation literature, and despite passing a cognitive screening, we found disproportionate transverse patterning deficits in impaired older adults. Forthcoming work should determine if transverse patterning performance is similar between impaired older adults and patients with Mild Cognitive Impairment. © 2016 Wiley Periodicals, Inc.